Case report: Uniportal video-assisted thoracoscopic sleeve lobectomy in a 6-year-old patient with inflammatory myofibroblastic tumor (IMT) - Geng, Zhen-Yang; Li, Zi-Hao; Li, Shi-Hao; Wu, Bin; Sheng, Yin-Liang; Yuan, Ping; Li, Feng; Qi, Yu (Frontiers in Pediatrics, 2023)
Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm that can occur in various organs, including the lung. Surgical resection is usually the preferred treatment for localized IMT.A 6-year-old female was admitted to our hospital with complaints of "coughing and vomiting for 6 days". A chest CT scan revealed occlusion of the left main bronchus, segmental atelectasis of the left lower lung, and cystic low-density shadows along the bronchial pathway. Subsequent fiberoptic bronchoscopy confirmed the diagnosis of IMT through pathological biopsy. After excluding surgical contraindications, the patient underwent uniportal video-assisted thoracoscopic sleeve lobectomy for treatment. The patient had an uneventful postoperative course and was discharged four days after surgery. After one month, the patient received a follow-up examination and reported no significant discomfort. A chest CT scan revealed no postoperative complications.Our experience suggests that uniportal video-assisted thoracoscopic surgery may be a safe and effective approach for the treatment of pediatric patients with IMT requiring complex surgical procedures such as sleeve lobectomy and tracheoplasty.